Human factors considerations in designing a personalized mobile dialysis device: An interview study. (May 2020) - Kim, Ji-Eun; Kessler, Larry; McCauley, Zach; Niiyama, Itsumi; Boyle, Linda Ng
Abstract: Recent technical advances have enabled the creation of mobile dialysis device prototypes. These prototypes have been tested for their ability to allow an individual to be dialyzed continuously rather than sporadically. The most recent prototype of a mobile dialysis device aims at increased functionality, which suggests that human factors issues (e.g., efficiency, bulkiness, and weight) are now considered carefully. This study describes advances in the design of an Ambulatory Kidney to Improve Vitality (AKTIV), using an interview protocol during the early stages of product development to capture patients' and caregivers' reactions. The AKTIV has the potential to improve patients' quality of life and decrease mortality rates. The goal of our study is to examine patients' and caregivers' design preferences and feature considerations for an AKTIV. We interviewed 22 participants (age M  = 57.50, SD  = 13.30), of whom 12 were female and 16 were patients. A pre-interview survey was distributed to the participants, and semi-structured interviews were subsequently held. The pre-interview results show that the belt and backpack designs were preferred over the shoulder bag and distributed designs. The participants also indicated on their pre-interview forms that safety and accuracy were more important to them than attachment ease, comfort, compactness, or operational simplicity. Invisibility and mobility were frequently mentioned when determining the strengths of each of the five design types during the interviews. Finally, individual differences in preferences for the various design types and attributes were identified. The results from our study have important implications for improving efficiency, effectiveness, and user satisfaction in relation to AKTIV prototypes and products. The findings from this interview study will help to ensure engineers and clinicians have target parameters for redesigning the AKTIV. Highlights: The belt and backpack designs were preferred over the shoulder bag and distributed designs, and safety and accuracy were more important than attachment ease, comfort, compactness, or operational simplicity. Invisibility and mobility were frequently mentioned when determining the strengths of each of the five design types during the interviews. Individual differences in preferences for the various design types and attributes were identified.